Inhibitory Effects of Petai Peel Extract Gel on Tyrosinase and TRP1 Gene Expression in UVB-Exposed Mouse Skin - Hutabarat, Nenny Lynda Caroline; Subchan, Prastyowati; Putra, Agung; Amalina, Nur Dina; Sitompul, Faya Nuralda (Stem Cell and Cancer Research (SCCR), 2023)
Background: UVB irradiation can induce the formation of Reactive Oxygen Species (ROS), which causes the activation of melanin synthesis through the activation of tyrosinase and tyrosinase-related protein-1 (TRP1). Secondary metabolites in stink bean peel extract inhibit ROS production due to exposure to UVB rays. This study aims to determine the effect of administering stink bean peel extract gel on the expression of the tyrosinase and TRp1 genes in mouse skin tissue exposed to UVB. Method: The research design was a posttest-only control group with a completely randomized design method. The samples studied were 24 mice exposed to UVB light with a wavelength of 302 nm and an energy of 390mJ/cm2/day 3 times a week for 2 weeks. This research was carried out in four groups: the healthy group, the negative control group, treatment 1 (T1) with 10% stink bean peel extract gel, and treatment 2 (T2) with 20% stink bean peel extract gel. Tyrosinase and TRP1 gene expression were analyzed using qRT-PCR. Results: qRT-PCR analysis showed that there was a significant decrease in tyrosinase and TRP1 gene expression between groups T1 (tyrosinase 3,19±2,12 and TRP1 4,96±3,42) and T2 (tyrosinase 0,65±0,44 and TRP1 2,22±1,18) compared to negative control (tyrosinase 17,92±3,77 and TRP1 35,91±4,52). Conclusion: The administration of stink bean peel extract gel has shown promising results in reducing the expression of tyrosinase and TRP1 genes in hyperpigmentation mice exposed to UVB light. This suggests that stink bean peel extract could be a safe and effective therapeutic approach for preventing UVB-induced hyperpigmentation.